Diffusion equations in inhomogeneous solid having arbitrary gradient concentration - Bilotsky, Y.; Gasik, M.; Lev, B. (Condensed Matter Physics, 2017)
A quantum kinetic equation is obtained for an inhomogeneous solid having arbitrary gradient concentration and chemical potential. We find, starting from nonequilibrium statistical operator, a new equation to describe atom migration in solid states. In continuous approximation, this equation turns into a non-linear diffusion equation. We derive conditions for which this equation can be reduced to Fick’s or Cahn equation. Виведено кiнетичне рiвняння дифузiї i знайдено хiмiчний потенцiал для дифундуючих атомiв в неоднорiдному твердому тiлi при довiльному градiєнтi концентрацiї. Базуючись на нерiвноважному статистичному операторi, знайдено нове рiвняння, що описує мiграцiю атомiв в твердому тiлi. Отримане рiвняння в неперервному випадку перетворюється в нелiнiйне рiвняння дифузiї, яке при вiдповiдних умовах може бути трансформоване у добре вiдомi рiвняння Фiка або Кана. Отримано вiдповiднi розв’язки для таких рiвнянь.